Quality of life of adolescents with type 1 diabetes (Clinics, 2015)
INTRODUCTION: Diabetes mellitus is a highly prevalent chronic disease. Type 1 diabetes mellitus usually develops during infancy and adolescence and may affect the quality of life of adolescents. OBJECTIVE: To evaluate the quality of life of adolescents with type 1 diabetes mellitus in a metropolitan region of western central Brazil. METHODS: Adolescents aged 10-19 years who had been diagnosed with type 1 diabetes mellitus at least 1 year previously were included. Patients with verbal communication difficulties, severe disease, and symptomatic hypo- or hyperglycemic crisis as well as those without an adult companion and who were ;7%. In general, the adolescents consistently reported having a good quality of life. The median scores for the domains of the instrument were as follows: “satisfaction”: 35; “impact”: 51; and “worries“: 26. The total score for all domains was 112. Bivariate analysis showed significant associations among a lower family income, public health assistance, and insulin type in the “satisfaction” domain; and a lower family income, public health assistance, public school attendance, and a low parental education level in the “worries“ domain and for the total score. A longer time since diagnosis was associated with a lower total score. Multivariable analysis confirmed the association of a worse quality of life with public health assistance, time since diagnosis, and sedentary lifestyle in the “satisfaction” domain; female gender in the “worries” domain; and public health assistance for the total score. CONCLUSIONS: Overall, the adolescents evaluated in this study viewed their quality of life as good. Specific factors that led to the deterioration of quality of life, including public assistance, time since diagnosis, sedentary lifestyle, and female gender, were identified. No potential conflict of interest was reported.